La importancia de la maternidad y la lactancia en los seis primeros meses de vida en el centro de educación inicial “Safari Kids” del cantón Riobamba - Amaguaya Vilema, Evelin Viviana (2024)
The main objective of this research project was to determine the importance of motherhood and breastfeeding in the first six months of life in the early childhood education center "Safari Kids" in the Riobamba canton. It is of great interest that mothers know about this topic and can put it into practice with their newborns. Therefore, this research project used bibliographic methodology, cross-sectional design field, non-experimental, and descriptive level. The study sample was made up of 18 mothers from sublevel II. The techniques used for data collection were a survey applied through a website, so it is divided into two sections, knowledge and practices, where it is evident that the mothers of the institution have a certain percentage of knowledge; therefore, the mothers act through their knowledge while some of them were shown not to put their knowledge into practice. Considering the results obtained, a proposal for creative educational material was developed through brochures and cards on the correct positions for breastfeeding the baby since this allows future mothers to know and act correctly, putting into practice and demonstrating the importance of motherhood and breastfeeding during the first six months of life, so this contributes to improving the lack of information that mothers currently have.